Whole genome resequencing-based analysis of plateau adaptation in Meiren yak (Bos grunniens) - Tong Wang; XiaoMing Ma; ChaoFan Ma; XiaoYun Wu; Ta ZhaXi; LiXin Yin; WeiGuo Li; YuFei Li; ChunNian Liang; Ping Yan (Animal Biotechnology, 2024)
The Meiren yak is an important genetic resource in Gansu Province, China. In this study, we aimed to explore the evolutionary history and population structure of the genetic resource of Meiren yak and to mine the characteristic genes of Meiren yak. We analysed a total of 93 yaks of eight yak breeds based on whole genome resequencing combined with population genomics and used θπ ratio and Fst method to screen the selected sites in the genome region. The results proved that Meiren yak can be used as a potential genetic resource in Gansu Province. The genes in Meiren yak with positive selection in selection signal analysis were subjected to the Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses, which indicated that the genes were related to the adaptability to high altitude and hypoxic environment. By analysing the genetic variation of Meiren yak at the genome-wide level, this study provided a theoretical basis for genetic improvement of Meiren yak and for the development of high-quality yak resources.